Screening for host responses in Acacia to a canker and wilt pathogen, Ceratocystis manginecans. Issue 1 (15th October 2017) - Trang, T. T.; Eyles, A.; Davies, N.; Glen, M.; Ratkowsky, D.; Mohammed, C.
Summary: In Vietnam, the productivity of Acacia hybrid ( Acacia mangium  x  A. auriculiformis ) plantations is being threatened by an aggressive canker pathogen, Ceratocystis manginecans, and selection for tolerance is the main control strategy. A pot trial was established in Binh Duong province to screen for the host response of nine Acacia genotypes (six Acacia hybrid clones, two A. auriculiformis clones and mixed provenance seedlings of A. mangium ) to artificial inoculation with three isolates of C. manginecans . Lesion lengths as measured on the inner bark suggested that the two A. auriculiformis clones were relatively more tolerant to C. manginecans than the A. mangium genotype. In contrast, the lesion lengths of all six Acacia hybrid clones fell between the A. auriculiformis and A. mangium genotypes. The results of this study indicate that among the Acacia hybrid clones, BV10 showed the most tolerance to C. manginecans . Chemical analysis of crude sapwood extracts sampled from the lesion provided some evidence that induced phenolic compounds, particularly tetrahydroxyflavanone and condensed tannins may have a defensive role in the Acacia — C. manginecans pathosystem. However, results were not consistent across individual Acacia hybrid clones and A. mangium genotypes.